The use of technological tools and virtual platforms to develop and improve the teaching process of a foreign language - Pineda Murcia, Gabriela Elizabeth
The use of digital technology with it continues developments has changed learning strategies and teaching methodologies due to the rigorous change of modality in the educational system in and out of the class because of covid-19 pandemic. For this, it is crucial that teachers consider in their methodology the implementation of virtual tools and its most outstanding characteristics to make the teaching-learning process more effective for their students. This study seeks to provide an insight about new technological resources by the professors in English foreign language instruction. It discusses the evaluation of how a strong educational management in the online teaching methods can improve the learning process of students from the University of El Salvador.To test the importance of a good online teaching training to ease the learning process of the foreign languages, diverse e-learning platforms were studied to know the different ways to carry out the teaching process. Furthermore, the results revealed that even if there are many virtual platforms to develop a class, professors must know how to make well use of different LMS platforms to fulfill the needs from the students. The report indicates that the effective use of educational technology tools improves the learning foreign language performance. Mastery of online teaching should be essential for smooth teaching-learning experience through virtual learning. Keywords: Online education; Virtual Environment; LMS platforms; E-learning; Learning theory; Technological tools.